2012
DOI: 10.2139/ssrn.2193650
|View full text |Cite
|
Sign up to set email alerts
|

The Roots of Export Diversification

Abstract: Countries with diversified export baskets take advantage of various benefits, which are said to foster and stabilize economic growth directly and through indirect channels (e.g. reduced income volatility, positive externalities, spillover effects). This is especially important in the context of developing economies. However, identifying the true determinants of export diversification is difficult as there exists no comprehensive theoretical or empirical framework to capture all potential factors in their entir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 37 publications
1
10
0
2
Order By: Relevance
“…Accordingly, the importance of export development and diversification as the new engine of growth (Samen, 2010) for developing countries cannot be overemphasized. However, identifying the true determinants of export diversification is difficult as there exists no comprehensive theoretical or empirical framework to capture all potential factors in their entirety (Jetter & Hassan, 2013). Consequently, the literature review identifies the range of factors used, the frequency with which they are used and their degree of significance in supporting or inhibiting export diversification.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, the importance of export development and diversification as the new engine of growth (Samen, 2010) for developing countries cannot be overemphasized. However, identifying the true determinants of export diversification is difficult as there exists no comprehensive theoretical or empirical framework to capture all potential factors in their entirety (Jetter & Hassan, 2013). Consequently, the literature review identifies the range of factors used, the frequency with which they are used and their degree of significance in supporting or inhibiting export diversification.…”
Section: Resultsmentioning
confidence: 99%
“…Education -There is a positive relationship between education and export diversification. In particular, total net enrollment in primary education is one of the two most important predictors of export diversification (Jetter & Hassan, 2013). Further, the literature reveals that higher levels of education in the labor force allow countries to take advantage of the higher income stemming from positive terms of trade shocks to develop new export sectors (Agosin et al, 2012).…”
Section: Human Capital and Demographic Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferrarini and Scaramozzino (2016) and Jetter and Ramırez Hassan (2013) have emphasized that the optimal size of the government and its increased effectiveness can lead to the creation of a diverse and inclusive set of productive goods by enhancing the quality of services and long-term investment in education. The effectiveness of government fiscal and budgetary policies and its active presence in the economy can be attributed to the high quality of public services, effective planning and implementation of policies and the credibility of government commitment to policies.…”
Section: Experimental Literature Reviewmentioning
confidence: 99%
“…(2017)Linking economic complexity, institutions, and income inequality; 122 countries including countries with a population greater than 1.5 million and total exports over one billion dollars, 1968–2008.The result was that increased economic complexity was associated with reduced income inequality, and countries exporting complex products had lower income inequality than countries exporting simple products.Gnangnon and Moser (2014)Intellectual Property Rights Protection and Export Diversification: The Application of Utility Model Laws; 89 Developing and Developing Countries, 1975–2003.The results showed that the protection of intellectual property rights, commercial freedom, innovation, and an increase in GDP and human capital leads to diversification of export products and consequently economic complexity.Pugliese et al. (2014)The discernment of heterogeneous country industrialization patterns through economic complexity; India, 1963–2012.The results show that more complex and diverse economies when experiencing industrialization, fewer constraints on per capita GDP.Jetter and Ramırez Hassan (2013)The Roots of Export Diversification;Selected Countries of the World,1960–1960.The results showed that out of the 43 factors examined, only four factors: natural resource costs as a percentage of GDP, primary school enrollment rate, population size and level of foreign direct investment are important in long-run export diversification.Agosin et al. (2012)Determinants of Export Diversification around the world; Selected countries of the world, 1962–2000The results show that the effect of distance to market variables and trade openness have negative effects on export diversification and the effect of education and human capital is positive and significant.Parteka and Tamberi (2011)Export diversification and development - empirical assessment; 60 selected countries, 1985–2004.The empirical findings show that relatively high expertise in economic structures is associated with low levels of per capita income, but countries diversify their export structures as they grow.…”
Section: Experimental Literature Reviewmentioning
confidence: 99%